Do labour taxes and their composition affect wages in the short and the long run? - Arpaia, Alfonso; Carone, Giuseppe; European Commission : Directorate-General for Economic and Financial Affairs (Brussels ; Belgium : European Commission: Directorate-General for Economic and Financial Affairs, 2004)
Measures aimed at reducing the tax burden on labour have been advocated to alleviate the EU unemployment problem. Most of the analyses document a relationship between the unemployment rate and the tax burden on labour. Hence, it is not possible to discern whether the effect on unemployment derives from labour demand, labour supply or through the wage formation mechanism. Moreover, the empirical analyses are usually static, and may be indicative of the steady-state determinants of the unemployment rate and do not reveal the features of the adjustment process. This paper studies the relationship between labour taxes and labour costs by modelling the wage formation mechanism in a dynamic context. We test if the composition of labour taxes affects labour costs in the short- and in the long-run and whether highly centralised bargaining systems have better employment performance than decentralised ones. We apply static and dynamic panel data techniques to a panel of EU countries. Our findings suggest that there is probably some wage resistance in the short-term but not in the long-term, although the transition to the long-term can be very long and therefore the short-term impact and the dynamics of adjustment can be long-lasting.
Internal paper
Economic Papers